Kształcenie policjantów w Stanach Zjednoczonych (wybrane podejścia i tendencje) - Andraszczyk , Wojciech (Studia Edukacyjne, 2017)
The article reconstructs selected contexts of police training in the United States of America. The narration concentrates on the historical origins of police training as well as on the dominant relevant trends in presentday American society. Furthermore, the paper seeks to compare the two ways of thinking about police training which influencethe training programs in police academies. The author presents methods of shaping the identity of policemen, the firstof which is a military model and the second one is an academic model. The text focuses moreover on the evolution of the operating system of the American police: from intervention-oriented to a community-oriented model, which is constantly gaining importance in some police training programs.